Effectiveness of Antenatal Counselling in Increasing the Acceptability and Insertion of Postplacental IUCD in Postpartum - Ghazala Shams,, Nomia Ashraf, Tooba Moon, Nazia Sajjad,, Maham Waseem, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate effectiveness of antenatal counselling in increasing the acceptability and insertion of Post Placental Intrauterine Contraceptive Device in postpartum women Study design: Prospective study. Place and duration of study: Department of Obstetrics & Gynaecology, Hayatabad Medical Complex, Peshawar from 1st April 2022 to 30th September 2022. Methodology: Fifty pregnant women were enrolled. The age of the pregnant women was taken within 18-43 years. The couples were counselled for the uptake of PPIUCD through gynaecological professional assistance. The counselling was done at 28 weeks followed by at 36 weeks. The misconceptions and myths were eradicated through the use of one-to-one interview as well as focus group discussions. The fears of the patients and their spouse were addressed through detailed discussion. Results: The mean age was 24.8±4.06 years. There were 70% of the pregnant women who agreed to get PPIUCD inserted, however only 42% actually underwent the procedure. Majority of the cases were within the age group of 18-28 years. The reasons recorded for not getting PPIUCD insertion previously presented data where 23% of the pregnant women had no awareness provided about PPIUCD before while 13% preferred other contraceptive methods. Conclusion: The outcomes of the antenatal counselling are higher uptake of post placental intrauterine contraceptive device with a rate of 42% increase in post-partum women. There is an evident reduction in misconceptions and myths about post-placental intrauterine contraceptive device through antenatal counselling. Key words: Antenatal counselling, Outcome, Intrauterine contraceptive device, Post-partum